1981
DOI: 10.1104/pp.67.6.1156
|View full text |Cite
|
Sign up to set email alerts
|

Ureide Synthesis in a Cell-Free System from Cowpea (Vigna unguiculata [L.] Walp.) Nodules

Abstract: Tbe effect of°2 and pH on the in vitro synthesis of IC-labeled ureides from IS-Clhypoxanthine in a cell free system from cowpea nodules was investigated. Under conditions which suppressed uricase (EC 1.733) activty, namely low 02 concentrations and low pH, ureide synthesis was inhibited and the 'C label incorporated into uric acid was increased. Conversely, conditos which increased uricase actinty, namelY high 02 concentrations and high pH, also stimulated ureide synthesis, and the 'C label was incorporated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Studies with cell-free extracts of cowpea and soybean have demonstrated that these compounds are formed from the oxidation of purine bases and nucleotides (1,4,17,19,20) derived by a pathway of de novo purine synthesis which utilizes products of N2 fixation (5). Although IMP has been detected as the initial nucleotide product of de novo purine synthesis in cowpea nodules (5), it is not clear whether IMP is metabolized principally through inosine and hypoxanthine or through oxidation to XMP2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with cell-free extracts of cowpea and soybean have demonstrated that these compounds are formed from the oxidation of purine bases and nucleotides (1,4,17,19,20) derived by a pathway of de novo purine synthesis which utilizes products of N2 fixation (5). Although IMP has been detected as the initial nucleotide product of de novo purine synthesis in cowpea nodules (5), it is not clear whether IMP is metabolized principally through inosine and hypoxanthine or through oxidation to XMP2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Since the enzymes of de novo purine synthesis and uricase were found in both cell types, Shelp et al (21) concluded that both cell types were capable of ureide synthesis. However, Shelp et al (21) proposed that uricase may be active only in the uninfected cells in vivo owing to the 02 requirement for the uricase reaction (30) and the presence of the 02-binding protein, Lb2, in the infected cells (22).…”
mentioning
confidence: 99%
“…The catabolic route to ureide biogenesis is supported by the following observations: 1. high levels of xanthine (XAN) dehydrogenase, uricase, and allantoinase activity are present in nodules of cowpea (2, 5, 7), soybean (40, 41, 115, 135), and garden bean (102,105,136,137); 2. the levels of these enzymes are normally low in nodules of amide-exporting legumes such as lupin (102,105) and pea (28); 3. the levels of these enzymes increase in response to the onset of N2 fixation, NH4 + assimilatory activity, and ureide export within the nodule (2,5,7,105,115); and 4. the addition of allopurinol, an irreversible inhibitor of XAN dehydrogenase, results in a decrease in the levels of ureides in nodules and ureide export in the xylem and an increase in XAN in the nodule (2,5,40,142). The ability of cell-free extracts of nodules to convert intermediates such as IMP, XMP, XAN, and hypoxanthine into ureides and for allopurinol to block this conversion (142,152,153) substantiate the competency of nodules to form ureides via purine oxidation.…”
Section: Biogenesis Of Allantoin and Allantoic Acidmentioning
confidence: 84%
“…Label from e4C]GL Y, a purine precursor, was incorporated into ureides (152,153) in cell-free extracts of cowpea nodules. These results are consistent with the role of de novo purine synthesis but do not discount a condensation mechanism of synthesis.…”
Section: Biogenesis Of Allantoin and Allantoic Acidmentioning
confidence: 99%